(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
Since 1983 up to today the archaeological researches of Macerata University at Gortyn (Crete) have been concentrated with special attention on investigations of Byzantine Quartier (so-called Byzantine Houses), westward from Pretorio and West Road, which the same Pretorio and the Quartier faces. The current finalities of research activities concerned the so-called Sud Building in the south-oriental area of Quartier which, till now, has hallowed to attain a punctual and detailed planimetry and a definition of main chronological phases of the monument (from his foundation at the last decades of IV century A.D., to his final destruction with the 670 earthquake), while are still themes of investigations his function (clearly of public destination) and his connection either with the wide West Road, or with the surrounding urbanistic complex. A goal of ongoing studies is represented also by final edition of excavations, of years 1983-1991, in the inhabited area with craftsmen houses and shops, which has produced remarkable contributions either about analysis of the Crete urban installation models between V- VIII centuries A.D. Particular interest was placed on the study, here showed, of ceramic materials regarding the same chronological phases.